The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s11096-019-00897-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of mental health clinical pharmacist independent prescribers within general practice in remote and rural Scotland

Abstract: Background A 12-month pilot was implemented in two general practices in remote and rural Scotland, with patients referred by general practitioners to specialist mental health pharmacist independent prescribers. Objective The objective was to evaluate the pilot service from the perspectives of the patients and the care team. Methods The pharmacists routinely recorded patient-specific data of all clinical issues and their actions at the time of each consultation. Further datasets comprised baseline and follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…For primary care managed patients, GP practice-based pharmacists are widespread in the UK and are currently being piloted in Ireland as part of a research study (Cardwell et al 2018). They may find a role in mental health services, similar to their role in the UK in the future (Buist et al 2019). These efforts will require new partnerships, seamless use of technology and the dismantling of antiquated roles and regulations alongside leadership from the health service for expansion if benefits in health outcomes are shown.…”
Section: Opportunities For Further Role Development and Recommendationsmentioning
confidence: 99%
“…For primary care managed patients, GP practice-based pharmacists are widespread in the UK and are currently being piloted in Ireland as part of a research study (Cardwell et al 2018). They may find a role in mental health services, similar to their role in the UK in the future (Buist et al 2019). These efforts will require new partnerships, seamless use of technology and the dismantling of antiquated roles and regulations alongside leadership from the health service for expansion if benefits in health outcomes are shown.…”
Section: Opportunities For Further Role Development and Recommendationsmentioning
confidence: 99%
“…The present paper lays out views from one important sector of health care provision that is often underrepresented, the consumer. In New Zealand and overseas, individuals generally express positive views of their experience using advanced practitioner services [ 10 , 30 38 ]. Yet, our study suggests that participants struggled to ‘position’ advance practitioners as a health care delivery cog, and described them as operating ‘below’ GPs but ‘above’ traditional nursing or pharmacy roles.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants indicated that they were not always able to perceive differences between NPs/ PPs and medical doctors. Based on this finding, caution is potentially needed when interpreting end-user satisfaction and quality of experience with advanced practitioner services [ 10 , 30 38 ]. Where people do not recognise a difference between provider types, they are unlikely to ‘measure’ the quality of the services they receive accurately.…”
Section: Discussionmentioning
confidence: 99%
“…This reluctance to provide support has been seen in previous research. 25 , 44 A possible explanation for this is that GPCPs were recommended to GPs to save time in practice; however, research indicates that pharmacists commencing employment within General Practice require time and support from GPs to help with their initial development. 2 , 15 Research suggests that pharmacists who are supported and integrated sufficiently are most effective, resulting in GPs acknowledging their usefulness.…”
Section: Discussionmentioning
confidence: 99%